Integration of areas of artistic orientation in children's creativity - Stulikova N. A., Babchenko T. S., But I. S. (Education and science in the modern context, 2020)
The inclusion of integrated lessons with elements of improvisation in the learning process is an innovation in modern pedagogical practice. The article discusses the option of conducting an integrated lesson "Visual activity - choreography", which consists of two parts and is conducted by two teachers.
Keywords: изобразительная деятельность; хореография; инновационный подход; интегрированное занятие; choreography; an integrated lesson; нетрадиционные формы работы в дополнительном образовании; инновации в современной педагогической практике; элементы импровизации; сюжетный танец и музыка; non-traditional forms of work in additional education; visual activity; innovations in modern pedagogical practice; an innovative approach; elements of improvisation; plot dance and music